"There Will Be No Agroecology Without Feminism":: Â The Brazilian Case - Prévost, Héloïse; Esmeraldo, Gema Galgani Silveira Leite; Guetat-Bernard, Hélène (Sustainability in Debate, 2014)
The vital contribution of smallholders’ production to agroecosystems and to food security leads to the valorisation of agroecology. However, a gender perspective is usually lacking when talking about those issues. In a context of a changing climate and the advancement of corporate agriculture, this essay analyses the Brazilian case to create awareness about the importance of rural women and feminist movements in food security and agroecology. This essay discusses women’s role in smallholder’s production, agrobiodiversity and agroecology.